Investigating the Effect of Business Leaders’ Management Style on a Family Business Company Growth Rates Among Selected Small and Medium Size Enterprises in Singapore - Yee Wen, Tan (Digital Repository of Theses - SSBM Geneva, 2024)
Family businesses are a vital part of the economy in Singapore and effective leadership in the company enables success and growth over time. The leaders in a family business, the founder, and the next generation successor, are crucial to the business because they must lead the company to realise a company's key performance indicators and objectives. The study explores the type of leadership of founders and next generation successors in Singapore. The literature review investigates leadership and company growth objectives, leadership frameworks, types of leadership and measurement tools of leadership approaches in family businesses. Leadership frameworks such as the MLQ (5X), determine whether a company leader has a Transformational, Transactional, or Passive- Avoidant approach. The literature review discusses the measurements of Financial and Non-Financial Performance that documents a business goals and growth. Current academic research shows that leadership approaches of founders and successors are a vital aspect for the company. A leader implements a certain leadership style to guide their employees at work towards better performance. This study explores types of leadership, effectiveness to achieve comparatively higher company growth rates, and non-financial objectives of the family business. In addition, this study focuses on the founder and the working successor during the succession transition in a family business. Lastly, Financial and Non-Financial Performance is applied to measure the company growth as a comparison with the company‟s closest competitor based on the point of view from the leader‟s self-assessment. The data of the research contributes beneficial insights for the Singapore family business industry and for stakeholders who are keen in the relation between leadership and company growth. The data can be used by family business leaders in similar situations and professional consultants to improve the leadership style of leaders in small and medium size enterprises (SMEs) and give access to further research in the Singapore family business context. viii